Preparation and preliminary studies of porous fish collagen and chitosan materials enriched with microcapsules containing an active ingredient - Justyna Kozlowska; Agnieszka Ciesielska (Scientific Reports)
Abstract This study explores the development and characterization of advanced composite materials combining fish collagen and chitosan, enhanced with chitosan-based microcapsules encapsulating an active ingredient—Calendula officinalis flower extract—hrough ionic gelation using various surfactants (Span 80, Tween 80 and Span80/Tween 80). Collagen was successfully extracted from northern pike scales and integrated with chitosan to create porous, three-dimensional matrices by the lyophilization process. Various amounts of microcapsules were incorporated into the matrices, and the structure of the obtained materials, their mechanical properties, swelling capacity, and susceptibility to degradation were assessed. Matrices with microcapsules exhibited high porosity, substantial swelling capacity, and improved mechanical properties compared to matrices without them. Microcapsules enabled the controlled release of active ingredients, demonstrating potential applications cosmetic industry. This research aligns with current trends in the cosmetics industry, such as the use of sustainable and eco-friendly materials derived from renewable resources like fish waste, the emphasis on natural and bioactive ingredients such as plant extracts, and the development of advanced delivery systems for controlled release of active compounds. The study addresses consumer demand for biodegradable and non-toxic materials, reducing environmental impact while enhancing product efficacy and safety.